2006
DOI: 10.1007/s00404-006-0197-0
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi disease during pregnancy

Abstract: This is the fourth reported case of Kikuchi disease developing during pregnancy. When Kikuchi disease occurs in a pregnant woman, there is neither any effect of disease on the pregnant woman nor the fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“… 2–9 In these cases, no miscarriages were communicated. In some cases 2,6,9 KFD was diagnosed before pregnancy and it recurred during the next pregnancy. In our case, KFD was diagnosed outside of pregnancy and the patient suffered a new bout during the first trimester of her third pregnancy.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“… 2–9 In these cases, no miscarriages were communicated. In some cases 2,6,9 KFD was diagnosed before pregnancy and it recurred during the next pregnancy. In our case, KFD was diagnosed outside of pregnancy and the patient suffered a new bout during the first trimester of her third pregnancy.…”
Section: Discussionmentioning
confidence: 88%
“…Recurrences during pregnancy have been described in four cases with good maternal and fetal outcomes 2,6,8,9 . There are scarce data concerning therapeutic requirements for this disease during pregnancy 5,6,9 . Recommended treatment is generally symptomatic, beginning with non‐steroidal anti‐inflammatory drugs (NSAIDs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, KFD is difficult to diagnose with fine-needle aspiration (13,54–57). Although recurrent lymphadenopathy suggests a diagnosis of KFD on clinical grounds, this may not be confirmed by pathological examination following LN excision (13,51), and some studies have reported a diagnosis of recurrent KFD based on clinical findings alone, without rebiopsy (3,13,42,51,58). The diagnostic criteria for recurrent KFD are therefore obscure.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is confirmed by lymph node biopsy, when histopathology reveals necrotizing lymphadenitis restricted to the cortical and paracortical areas, with partial or complete loss of follicular architecture, marked karyorrhexis and absence of neutrophils, granulomatous reaction or lymphoma cells [5]. Most KFD cases improve within a six-month period [3], and a wide range of recurrence rates have been reported, from 4% to 27% [10-12]. …”
Section: Discussionmentioning
confidence: 99%